Friends. Season 2 [videorecording (DVD)] - Crane, David, 1957-; Kauffman, Marta, 1956- (Distributed by Warner Home Video, 2010)
Rachel attempts to become more than friends with Ross, Joey's acting career takes off, and Monica begins dating a divorced older man.